Factors influencing HIV progression in a seroconverter cohort in Madrid from 1985 to 1999. Issue 4 (1st August 2002) - Del Amo, J; Del Romero, J; Barrasa, A; Pérez-Hoyos, S; Rodríguez, C; Díez, M; García, S; Soriano, V; Castilla, J
Abstract : Objective: To study HIV progression from seroconversion over a 15 year period and measure the population effectiveness of highly active antiretroviral therapy (HAART). Methods: A cohort study of people with well documented dates of seroconversion. Cumulative risk of AIDS and death were calculated by extended Kaplan-Meier allowing for late entry. Cox proportional hazards models were used to study variables associated with HIV progression. To assess the impact of HAART, calendar time was divided in three periods; before 1992, 1992–6, and 1997–9. Results: From January 1985 to May 2000, 226 seroconverters were identified. The median seroconversion interval was 11 months, median seroconversion date was March 1993. 202 (89%) were men, 76% of whom were homo/bisexual. A 66% reduction in progression to AIDS was observed in 1997–9 compared to 1992–96 (HR 0.34 95% CI: 0.16 to 0.70). People with primary education appeared to have faster progression to AIDS compared to those with university studies (HR 2.69 95%CI: 1.17 to 6.16). An 82% reduction in mortality from HIV seroconversion was observed in 1997–9 (HR 0.18 95% CI: 0.05 to 0.68) compared to 1992–6. Progression to death for people with primary education was twice as fast as for those with university education (p 0.0007). People without confirmation of an HIV negative test had faster progression (HR 4.47 95% CI: 1.18 to 16.92). Conclusions: The reduction in progression to AIDS and death from seroconversion from 1992–6 to 1997–9 in Madrid is likely to be attributable to HAART. HIV progression was faster in subjects with primary education; better educational level may be associated with better adherence to medication.